Stilistic Study Of Poetry Anthology “Aku Ingin Menjadi Peluru” Wiji Thukul's Works - Yuannisah Aini Nasution; Mei Nanda Sari (CV. AFDIFAL MAJU BERKAH, 2021)
This research focuses on study of diction, style of language, and imagery in the anthology of poetry